The Existence of Taman Siswa Amidst the Domination of Colonial Education in the Dutch East Indies - Iswahyudi Iswahyudi (RIRAI Publisher, 2023)
Taman Siswa, which was founded in 1922, aims to achieve a nation state that must and can be achieved through education. It also regenerates the native population so that it can throw off its colonial constraints and control its own political, social and economic development. In the first years of its existence, this organization was relatively unnoticed by the nationalist movement or by the colonial government. Taman Siswa's role in the constellation of the colonial state was to advance education for the native population because this institution functioned as a rival institution to the colonial government by rejecting the education system run by the colonial government and continuously trying to define Indonesia and the type of national education system that it was. ideal. The concept of Taman Siswa education was actually to adapt teaching to local values and customs, and at that time it prioritized Javanism rather than Indonesian nationalism itself. This is in accordance with one of the principles of Taman Siswa education, namely cultural nationalism. Ki Hajar Dewantara's educational ideas were largely influenced by many current discussions regarding education in the Netherlands itself as part of a wider global discourse.